Efektivitas Model Pembelajaran Problem Based Learning Berbasis Wordwall untuk Meningkatkan Critical Thinking Peserta Didik pada Materi Perumusan Dasar Negara Pancasila - Ruhiyat, Moch. Zian; AR, Endang Danial; Masyitoh, Iim Siti (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This study aims to evaluate and compare the effectiveness of the Wordwall-based Problem Based Learning (PBL) model and traditional lecture-based learning in enhancing students' critical thinking skills. Proficiency in critical thinking is crucial for effectively analyzing issues and proposing viable solutions. The PBL approach is particularly suited to developing students' critical thinking abilities by stimulating their cognitive skills and fostering consistent critical thinking practices. The research employed a quantitative methodology within a quasi-experimental framework, utilizing a non-equivalent control group design with 35 students in both the experimental and control groups. Data collection involved tests and observations, and analysis included descriptive analysis and prerequisite tests for normality and homogeneity. The statistical analysis used a paired sample t-test. Findings revealed significant differences between the experimental and control groups, with the experimental group showing higher average n-gain values (0.57 vs. 0.07) and percentages (56.85% vs. 6.70%), indicating greater effectiveness in improving critical thinking skills.